8(y-3)+7(y+2)=95

Simple and best practice solution for 8(y-3)+7(y+2)=95 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(y-3)+7(y+2)=95 equation:


Simplifying
8(y + -3) + 7(y + 2) = 95

Reorder the terms:
8(-3 + y) + 7(y + 2) = 95
(-3 * 8 + y * 8) + 7(y + 2) = 95
(-24 + 8y) + 7(y + 2) = 95

Reorder the terms:
-24 + 8y + 7(2 + y) = 95
-24 + 8y + (2 * 7 + y * 7) = 95
-24 + 8y + (14 + 7y) = 95

Reorder the terms:
-24 + 14 + 8y + 7y = 95

Combine like terms: -24 + 14 = -10
-10 + 8y + 7y = 95

Combine like terms: 8y + 7y = 15y
-10 + 15y = 95

Solving
-10 + 15y = 95

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '10' to each side of the equation.
-10 + 10 + 15y = 95 + 10

Combine like terms: -10 + 10 = 0
0 + 15y = 95 + 10
15y = 95 + 10

Combine like terms: 95 + 10 = 105
15y = 105

Divide each side by '15'.
y = 7

Simplifying
y = 7

See similar equations:

| 4x^4+16x^2-20=0 | | 3n^2-11n-14=0 | | 2x^2+7x=4x | | -7-7+1= | | sqrt9x^4y^5/sqrt18xy^3 | | -1/4x=64 | | 2x+18+3x-4=54-3x+32 | | 126399.2163=1/3*b*124.9 | | -x+4y=27 | | 5(4a+5b)-3(a+7b)= | | (2w^2-5w-7)-(6w^2+4w-4)= | | k=-1+7x | | 8+2=10+x | | k=8x-1+-1x | | x=66+-0.5y | | (2w^2-5-7)-(6w^2+4w-4)= | | x^2+10x+25+y^2-10y+25=1 | | x+(x-18)+(y-18)=96 | | 2/3x=1/3 | | 5m+8=12 | | x^2+y^2+10x-10y-49=0 | | by^2-2ay+3c=0 | | 20=.65x+c | | 9542.4=1/3*B*49.7 | | 2y+3=4y-1 | | 84.966=1/3*26.01*h | | (9+9)+8= | | (-4)x=-12 | | (x-18)+(y-18)+x=96 | | x+9=67 | | 5y/3=7y/6 | | x/6=4/21 |

Equations solver categories